Associated Branched Continued Fractions with Two Independent Variables - Dmytryshyn, R. I. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
An algorithm for the expansion of a given formal double power series in the associated branched continued fraction with two independent variables is constructed and the conditions for the existence of this expansion are established.